Forensic Unraveling the Unique: Investigating Peculiarities in Different Signature Styles - Sharda Yadav; Vinny Sharma; Suneet Kumar (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Every individual owns their specific style of doing the act of writing. The style is an acquired skill that grows during the learning process through the related environment. Nowadays, it has become common for white-collar crime offenders to deliberately incorporate different styles for their illegal benefit in writing, which gives the effect of execution by more than one author. Handwriting and signature identification have always been the primary part of the forensic examination of questioned documents. These types of distinct signatures always hold major complexity in their examination and can be confusing with the outcome of different authors, especially if a similar style has not been incorporated into the standard exhibits. As such, it has become a challenge for the forensic questioned document examiner to achieve that level of expertise where, despite adopting different styles, the author could easily be identified. Aim: So, this paper aims for an examination of the signatures engaged by the same individual who executes the signatures distinctively on every occasion and shows that they are executed by the same person. Objectives: To achieve this, a thorough examination was conducted. Material: handwriting characteristics were studied using the hand magnifier, protector, and a dimension scale. Result: which is helpful for forensic questioned document experts in forming a conclusive opinion, especially when exhibits of similar models and designs are not available. Conclusion: It is concluded that a detailed examination can lead to the common authorship, despite adopting different styles